Health Education as a Strategy for Early Prevention of Sexually Transmitted Diseases human immunodeficiency virus - Sudirman Sudirman; Rikwan Rikwan; Sitti Fajrah; Subardin AB; Fitriani Fitriani; Sri Purwiningsih (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: In 2021, 203 cases of HIV infection, or 58% of the estimated 350 people, were found in Sigi District. Commitment and collaboration from every sector continue to be carried out to achieve "three zero" HIV by 2030. IEC is the right strategy to prevent HIV at all levels of society, and effective communication strategies are used to deliver messages. This activity aims to increase the knowledge of school-age children related to HIV. Methods: This activity was carried out with the concept of socialization using the educational method for 2x45 minutes with 63 middle school-age students in the Palolo District, Sigi Regency. Measuring the knowledge of respondents was carried out by interviewing them using a questionnaire. By comparing the pre-test score with the post-test score for each question item, the higher the post-test score, the better the level of success achieved. Results: The results obtained indicate that the majority of students easily accept and understand HIV-related material about the meaning, transmission, risks, and prevention of HIV. Informational and educational communication through appropriate animation media can make it easier for students to learn about HIV and provide them with a good understanding of the virus. Conclusion: This activity concludes that students already have good knowledge about HIV after participating in socialization activities with educational methods using visual aids and media.